2005
DOI: 10.1021/ja043031t
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Selection of Lead Compounds by Click Chemistry:  Target-Guided Optimization of Acetylcholinesterase Inhibitors

Abstract: The target-guided, in situ click chemistry approach to lead discovery has been successfully employed for discovering acetylcholinesterase (AChE) inhibitors by incubating a selected enzyme/tacrine azide combination with a variety of acetylene reagents that were not previously known to interact with the enzyme's peripheral binding site. The triazole products, formed by the enzyme, were identified by HPLC-mass spectrometry analysis of the crude reaction mixtures. The target-guided lead discovery search was also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
0
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 326 publications
(202 citation statements)
references
References 54 publications
2
195
0
5
Order By: Relevance
“…Two nonquaternary pyridine aldoxime phenyltetrahydroisoquinoline derivatives directed to interact with the AChE peripheral site showed outstanding potency for in vitro reactivation of VX and tabun-conjugated hAChE (2). Thus, uncharged, extended ligands with high affinities for the peripheral site form an alternative means of directing nucleophiles to the organophosphate conjugated active center (28). The overall second order rate constant (k r ) for reactivation of VX-hAChE conjugate by phenyltetrahydroisoquinoline derivatives was an …”
Section: Oximementioning
confidence: 99%
“…Two nonquaternary pyridine aldoxime phenyltetrahydroisoquinoline derivatives directed to interact with the AChE peripheral site showed outstanding potency for in vitro reactivation of VX and tabun-conjugated hAChE (2). Thus, uncharged, extended ligands with high affinities for the peripheral site form an alternative means of directing nucleophiles to the organophosphate conjugated active center (28). The overall second order rate constant (k r ) for reactivation of VX-hAChE conjugate by phenyltetrahydroisoquinoline derivatives was an …”
Section: Oximementioning
confidence: 99%
“…[1][2][3] In addition, it was shown that the chemical modulation of the ethidium substituents is a profitable option to tune the nucleic acid recognition properties of phenanthridine dyes. [4] Very recent reports about numerous applications point toward versatility of the phenanthridine core, [5][6][7][8][9] including even intriguing biological activity. [10] A huge number of bis-phenanthridine derivatives were prepared with the aim of not only enhanced affinity due to the bis-intercalation into DNA/RNA but also with the idea of introducing selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…13). 106 Analysis of binary TZ2/acetylene mixtures with AChE revealed that only phenyltetrahydro-isoquinolines PIQ-A5 and PIQ-A6 formed significant amounts of triazole products identified as syn-isomers. Incubation of a mixture of 10 acetylene building blocks with TZ2 and AChE gave only expected triazole products TZ2PIQ-A5 and TZ2PIQ-A6 demonstrating the feasibility of multicomponent screening.…”
Section: -104mentioning
confidence: 99%